2007
DOI: 10.1196/annals.1396.005
|View full text |Cite
|
Sign up to set email alerts
|

Life Extension by Calorie Restriction in Humans

Abstract: Long-term reduction in energy intake in the diet (calorie restriction [CR]) extends the life of the laboratory rat by about 25%. However, in humans there are no life-long studies of CR, but only short-term trials which indicate that 20% CR acting over periods of 2-6 years is associated with reduced body weight, blood pressure, blood cholesterol, and blood glucose--risk factors for the major killer diseases of cardiovascular disease and diabetes. In addition, recent research has shown that CR for 6 months is ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…CR is widely used as a novel model for aging research. The latest research report indicated that dietary restriction can increase longevity in humans [89,90]. CR changes the endocrine and neuroendocrine systems in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CR is widely used as a novel model for aging research. The latest research report indicated that dietary restriction can increase longevity in humans [89,90]. CR changes the endocrine and neuroendocrine systems in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The Nrf proteins can induce expression of phase II detoxification enzymes in the liver and digestive tract in response to oxidative stress and xenobiotics [86,87,88]. During adulthood, SKN-1 involves resistance to damage induced by oxidative stress [89]. Therefore, SKN-1 could be a key regulator of the response to CR [76].…”
Section: Molecular Mechanism Of Cr Antiaging Responsesmentioning
confidence: 99%
“…Calorie restriction, not lipid restriction, has been shown to affect longevity in a wide range of species (Fontana et al 2010) but longevity studies of humans by humans are obviously impractical (Hursting et al 2010), the benefits are questioned relative to sanitation and modern medicine (Everitt and LeCouteur 2007), and a recent trial in primates failed to find an effect (Mattison et al 2012). It is well known that a low fat, low protein wholeplant diet, when supplemented with the essential nutrients vitamin B 12 and long-chain n-3 PUFA, has been associated with reduction of the thickness of cardiac arteries (Ornish et al 1998).…”
Section: Health Effects Of Fat As a Macronutrient And Energy Sourcementioning
confidence: 99%
“…mTOR1 is a master regulator of cell growth and metabolism and many pathways can converge to mTOR1 signaling, such as growth factors, which stimulate mTORC1 through the activation of the canonical insulin and Ras signaling pathways, energy status, oxygen levels, amino acids and other cellular conditions and signals [61,65]. Numerous studies have shown that reducing the mTOR signaling and energy metabolism can extend lifespan in many species [66,67]. Studies in mice also show that inhibition of the mTOR signaling pathway by rapamycin increases lifespan in genetically heterogeneous mice [68].…”
Section: Mtor Signaling and Energy Metabolismmentioning
confidence: 99%